2020
DOI: 10.2478/ebtj-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc and molybdenum on European Bluestar (Amsonia orientalis): An in vitro study

Abstract: This study aimed to investigate the effects of possible zinc (Zn) and molybdenum (Mo) contaminations on the critically endangered European Bluestar (Amsonia orientalis). The effects of Zn and Mo were tested in a dose-dependent manner on in vitro cultures. Zn at 0.1 mM in the medium inhibited root development whereas Mo showed the same effect only at ≥2.5 mM concentration. Gradual inhibition of shoot development was observed after treatment with both metals. Protein contents were also negatively affected by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Concerning soluble proteins content, it was mostly demonstrated that abiotic stress including heavy metals induce a decrease in this parameter in different plants (Farghali and Quronfulah, 2016;Acemi et al, 2020). The same result was shown in our work in the contaminated soil.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning soluble proteins content, it was mostly demonstrated that abiotic stress including heavy metals induce a decrease in this parameter in different plants (Farghali and Quronfulah, 2016;Acemi et al, 2020). The same result was shown in our work in the contaminated soil.…”
Section: Discussionsupporting
confidence: 90%
“…Data related to speci c activity of Peroxidase (POD) indicated that POD activity also depend upon the concentration of Pb ions and its time of application. Results of present work are in conformation with ndings for other plants under Pb stress as Jatropha curcas (Valadez-Villarreal, 2015) and European Bluestar (Acemi et al, 2020). Heavy metal stress in low concentrations for short time triggers POD activity but prolonged stress with high metal concentration results in enzyme inactivation (Lin et al, 2015) could be the reason of declining POD activity after certain period of time that was restored in ascorbic acid pretreated calli.…”
Section: Speci C Activity Of Superoxide Dismutase (Sod)supporting
confidence: 86%
“…Xu et al 15 found an increase in SOD, CAT, peroxidase (POD) and APX enzyme activities in the leaves and roots of soybean seedlings grown under extreme molybdenum stress. Acemi et al 57 determined that molybdenum exposure at doses of 2.5 mM and above caused increases in proline and MDA levels, and POD, SOD and CAT enzyme activities of Amsonia orientalis (blue star). Aragão et al 40 reported that environmental wastes containing trace elements such as Cu, Fe, Mn and Zn significantly increased SOD activity and decreased CAT activity in Allium cepa .…”
Section: Resultsmentioning
confidence: 99%
“…They stated that these antioxidants induced in plants act as protection against stress conditions. Acemi et al 57 showed that molybdenum exposure caused loss of integrity of root cell membranes in A. orientalis , resulting in MDA accumulation, and increased proline synthesis was not sufficient to maintain cell membrane stability. According to Xu et al 15 , elevated antioxidant enzyme activity in the roots and leaves of plants contributes to the tolerance of molybdenums in plants by maintaining the homeostasis of ROS.…”
Section: Resultsmentioning
confidence: 99%